Harvard Brain Death Criteria and Organ Transplantation: A Historical Revisit - Tham, L.C., Joseph (Studia Bioethica, 2011)
This article will examine the claims offered by both sides of the debate as to whether Brain Death definition was linked to Organ Transplantion needs by looking at historical studies on the relationship between them, either establishing such a link or rejecting it. In the last section, the role of Henry Beecher as the Committee chairman will be highlighted to put this debate in a proper perspective. Beecher is widely known for his role as a whistleblower of unethical experimentations on human subjects in the 1960s. His concerns for ethical behavior for scientists and physicians had an important impact on the Harvard committee, a role which has often been ignored.